Development of A. solani β-tubulin models and comparison of docking results for benzo[d]azoles derivatives as potential antifungal agents - Konstantin L. Obydennov; Tatiana A. Kalinina; Tatiana V. Glukhareva; Vasiliy A. Bakulev (Chimica Techno Acta)
An approach to developing a docking protocol using free software such as KNIME, DataWarrior, AutoDock Vina, AutoDockTools, OpenBabel and the SWISS-MODEL service was described. In particular, the process of generating possible isomeric structures using KNIME chemoinformatics libraries is described. A library of benzo[d]azoles containing 145 compounds with homologous models of Alternaria solani β-tubulin obtained in two ways: using the commercial Prime program and the free SWISS-MODEL service, the comparison of results was shown. Despite the less preorganization of the binding cavity of the homologous model obtained using SWISS-MODEL, the correlation of the results between the two methods were observed. The correlation coefficients were as follows: Pearson was 0.65, Spearman was 0.62. According to the docking results, 99% of the studied 2-aminobenzo[d]azoles derivatives showed a docking score of no more than –7, which indicates that these compounds are promising for studying the fungicidal activity, in particular against A. solani. Without taking into account pharmacokinetic characteristics, benzo[d]imidazole derivatives containing a sulfanilamidine substituent at the 2-amino group and thioacetyl derivatives of 2-aminobenzo[d]imidazole are of particular interest in the search for new antitubulin fungicides.